PENINGKATAN HASIL BELAJAR PAI DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DI SDN 2 PALAK TANAH MUARA ENIM - Elhefni Elhefni; Susilawati Susilawati (Ta'dib: Jurnal Pendidikan Islam, 2010)
Teachers are expected to increase quality of learning outcomes in the learning process. This research aims to know whether Cooperative Learning type of think pair can improve learning outcomes of Islamic religious subject. Based on data analysis it conclude that before deploying this learning model the frequency of the overall student learning outcomes as follows: 6 students (15%) is high (good), 26 students (65%) classified as medium, and 8 students (20%) is low. After application of the model the outcomes are as follows: high category (good) 4 people (10% of students), moderate 28 people (70% of students), and a low 8 people (20% of students).